The Setting as a Tool for the Conservation of Cultural Heritage: The Case of the Church of Our Lady of the Presentation in Porto Calvo/AL - Cunha, Claudia dos Reis e; Silva , Spartacus Soares da (Technical and Scientific Journal Green Cities, 2025)
Objective – This article analyzes the area surrounding the Church of Our Lady of Presentation, located in Porto Calvo, Alagoas, as an instrument for preserving cultural heritage. It considers the surroundings as an essential element in mediating between the cultural property and the contemporary city, marked by constant transformation. Based on this case study, the main challenges related to the management of areas adjacent to listed properties are discussed, as well as the role of these actions in promoting the protection and quality enjoyment of built heritage. The work also seeks to support the development of guidelines and regulations aimed at safeguarding the immediate surroundings of protected cultural properties.Methodology – The work will be developed through bibliographical studies and consultation of relevant legislation, combined with a field study conducted in the city of Porto Calvo, Alagoas, over the past few months. The proposed critical analysis will allow us to problematize the current methodological guidelines for delimiting the boundaries of listed properties, highlighting the need, in the specific case of the Church of Our Lady of Presentation, to incorporate new attributes capable of more effectively safeguarding the historical and cultural values ​​of the protected property.Originality/Relevance – The 1955 designation of the Church of Our Lady of Presentation lacks essential standards for the preservation and safeguarding of cultural heritage, such as delimiting the designation perimeter and surrounding area, and safeguarding guidelines for these areas. Therefore, the critical analysis proposed here could inform a process of re-ratification of the designation instrument, including regulations for the adequate protection of its surroundings, ensuring the visibility and ambiance of the designated property, thus making the designation more effective.Results – The expected results include critical reflection on the standards and guidelines capable of acting in the preservation and safeguarding of the Church of Our Lady of Presentation; problematization of the application of cultural heritage safeguarding instruments in urban environments in Brazil; and the need to understand the surroundings as an essential element for the enjoyment of cultural assets, even when individually listed.Theoretical/Methodological Contributions – This work is part of an ongoing research project, therefore, the results presented will be partial, but it is expected to point out some of the limitations of the process of safeguarding and managing the preservation of the Church of Our Lady of the Presentation of Porto Calvo, highlighting the need for a careful look at the surroundings as a fundamental element for the effective protection of the cultural asset.Social and Environmental Contributions The most significant implications for society, brought by this study, would be active monitoring and more effective guardianship, with a view to preserving the asset of collective interest.
Keywords: Cultural Heritage; Setting of Protected Cultural Heritage Sites; Church of Our Lady of Presentation in Porto Calvo/AL.